BIM-based construction simulation modelling - Osorio-Sandoval, Carlos Arturo (2021)
Construction simulation has been widely used in academia for research purposes and its usefulness as a planning and decision-making support tool has been proven. However, it has been neglected by the industry for various reasons, including the amount of data, skills, effort and time required to develop complex simulation models, the difficulty of model reuse, and the abstract and confusing way in which simulation results are usually presented.